2020
DOI: 10.1109/access.2020.3026968
|View full text |Cite
|
Sign up to set email alerts
|

Stages-Based ECG Signal Analysis From Traditional Signal Processing to Machine Learning Approaches: A Survey

Abstract: Electrocardiogram (ECG) gives essential information about different cardiac conditions of the human heart. Its analysis has been the main objective among the research community to detect and prevent life threatening cardiac circumstances. Traditional signal processing methods, machine learning and its subbranches, such as deep learning, are popular techniques for analyzing and classifying the ECG signal and mainly to develop applications for early detection and treatment of cardiac conditions and arrhythmias. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 147 publications
(122 reference statements)
0
70
0
Order By: Relevance
“…Einthoven in 1906 categorized normal and abnormal ECGs that were translated by Cardiologist Henry Blackburn [30]. He discussed the first electrocardiographic tracings of atrial fibrillation 3 , premature ventricular contractions 4 , ventricular bigeminy 5 , atrial flutter 6 . The beginning of ECG related research was also demonstrated in an experimental setup that induced heart block in a dog, as shown in Fig.…”
Section: Ecg Signal (P Wave Qrs Complex T Wave J Point)mentioning
confidence: 99%
See 2 more Smart Citations
“…Einthoven in 1906 categorized normal and abnormal ECGs that were translated by Cardiologist Henry Blackburn [30]. He discussed the first electrocardiographic tracings of atrial fibrillation 3 , premature ventricular contractions 4 , ventricular bigeminy 5 , atrial flutter 6 . The beginning of ECG related research was also demonstrated in an experimental setup that induced heart block in a dog, as shown in Fig.…”
Section: Ecg Signal (P Wave Qrs Complex T Wave J Point)mentioning
confidence: 99%
“…It also discusses the American observations of the ECG, the role of Thomas Lewis and the development of Electrocardiography, ECG and Myocardial Infarction (MI), precordial leads, and augmented limb leads, Vectorcardiogram in clinical physiology and the challenges of Electrocardiography. While these reviews focus on the historical development of the ECG, a recent review [4] focuses on various ECG signal processing research development that has occurred during 2000-2020. In [5], authors discuss several automatic detection methods for Myocardial Infarctions in their review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are inspired by prior work that uses autoencoders to generate features for signal classification [3,4]. Recent advancements in machine learning and available data have heralded an influx of multi-lead ECG classification algorithms [5,6,7,8,9,2]. We extend our prior work by using neural networks over feature engineering with gradient boosted tree classifiers [2].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, deep learning techniques have been gaining attention due to their powerful capability in learning the characteristics of ECG signal [23]- [27]. The noise suppression techniques based on denoising autoencoder (DAE) have shown the excellent performance than conventional denoising methods.…”
Section: Introductionmentioning
confidence: 99%